(untitled) (Web of Teachers: Inderscience Research, 2025)
Maqom art is a unique example of the national musical heritage of Central Asia, particularly in Uzbekistan, Tajikistan, and neighboring countries. This art form is distinguished by its complex melodic structure, unique performance techniques, and special vocal and instrumental styles. Melismatic singing, improvisation, and intricate rhythmic structures play a crucial role in Maqom performance. Additionally, the division of Maqom into the Fergana-Tashkent, Khorezm, and Bukhara-Samarkand schools highlights the diversity of performance styles across different regions. This article analyzes the technical and performance characteristics of Maqom art and explores its significance in musical culture.